A Standardized Classification Scheme for Gastroduodenal Disorder Evaluation Using the Gastric Alimetry System: Prospective Cohort Study - Chris Varghese; Gabriel Schamberg; Emma Uren; Stefan Calder; Mikaela Law; Daphne Foong; Vincent Ho; Billy Wu; I-Hsuan Huang; Peng Du; Thomas Abell; Charlotte Daker; et al. (Gastro Hep Advances)
Background and Aims: Gastric Alimetry™ (Alimetry, New Zealand) is a new clinical test for gastroduodenal disorders involving simultaneous body surface gastric electrical mapping and validated symptom profiling. Studies have demonstrated a range of distinct pathophysiological profiles, and a classification scheme is now required. We used Gastric Alimetry spectral and symptom profiles to develop a mechanism-based test classification scheme, then assessed correlations with symptom severity, psychometrics, and quality of life. Methods: We performed a multicenter prospective cohort study of patients meeting the Rome IV criteria for functional dyspepsia and chronic nausea and vomiting syndromes. Patients underwent Gastric Alimetry profiling, and a standardized digital classification framework was devised and applied to separate patients into those with a) abnormal spectral analyses (ie aberrant gastric frequencies, amplitudes, and rhythms); and normal spectral analyses with b) symptoms correlated to gastric amplitude (subgroups: sensorimotor, postgastric, and activity-relieved), and c) symptoms independent of gastric amplitude (subgroups: continuous, meal-relieved, meal-induced). Results: Two hundred ten patients were included (80% female, median age 37), of whom 169 met the criteria for chronic nausea and vomiting syndromes and 206 met the criteria for functional dyspepsia (79% meeting both criteria). Overall, 83% were phenotyped using the novel scheme, with 79/210 (37.6%) classified as having a spectral abnormality. Of the remainder, the most common phenotypes were “continuous pattern” (37, 17.6%), “meal-induced pattern” (28, 13.3%), and “sensorimotor pattern” (15, 7.1%). Symptom patterns independent of gastric amplitude were more strongly correlated with depression and anxiety (Patient Health Questionnaire 2: exp(β) 2.38, P = .024, State-Trait Anxiety Inventory Short-Form score: exp(β) 1.21, P = .021). Conclusion: A mechanistic classification scheme for assessing gastroduodenal disorders is presented. Classified phenotypes showed independent relationships with symptom severity, quality of life, and psychological measures. The scheme is now being applied clinically and in research studies.